Measuring and Modeling Stable Isotopes of Mobile and Bulk Soil Water - Sprenger, M. (2020)
The model included evaporation fractionation, allowed differentiation between a fast and a slow flow domain, and included isotopic exchange via water vapor. Our measurements showed that MW plots along the local meteoric water lines, whereas BW plots below, which is indicative of evaporation fractionation. We suggest that the relative volume of MW to BW is relevant for explaining these isotopic differences because MW volumes are usually relatively low during periods of high evaporation. Under this condition, differences between MW and plant water isotopes are not paradoxical but rather related to the water that cannot be sampled with suction lysimeters but is still available for plant water uptake. The simulations accounting for fast and slow flow supported the conceptualization of the two soil pore domains with isotopic exchange via vapor exchange because this model setup resulted in the best model performance. Overall, these findings are of high relevance for current understanding related to the source and isotopic composition of water taken up by plants.